Mental health in the global south: Challenges and opportunities in HCI for development - Pendse, Sachin R.; Karusala, Naveena; Siddarth, Divya; Gonsalves, Pattie; Mehrotra, Seema; Naslund, John A.; Sood, Mamta; Kumar, Neha; Sharma, Amit (ACM SIGCAS Conference on Computing & Sustainable Societies (COMPASS), 2019)
Mental illness is rapidly gaining recognition as a serious global challenge. Recent human-computer interaction (HCI) research has investigated mental health as a domain of concern, but is yet to venture into the Global South, where the problem exhibits a more complex, intersectional nature. In this paper, we review work on mental health in the Global South and present a case for HCI for Development (HCI4D) to look at mental health-both because it is an inarguably important area of concern in itself, and also because it impacts the efficacy of HCI4D interventions in other domains. We consider the role of cultural and resource-based interactions towards accessibility challenges and continuing stigma around mental health. We also identify participants' mental health as a constant consideration for HCI4D and present best practices for measuring and incorporating it. As an example, we demonstrate how both the process and the lens of aspirations-based design, a recently proposed approach for HCI4D research and design, may benefit from the consideration of mental health concerns. Our paper thus recommends a path forward for considering mental health in HCI4D, potentially leading to new research directions in addition to enriching existing ones.